2008
DOI: 10.1016/j.cub.2008.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Phosphorylation of Yeast Fus3 MAP Kinase Controls Periodic Gene Expression and Morphogenesis

Abstract: SUMMARY Signal transduction networks can display complex dynamic behavior such as oscillations in the activity of key components [1-6], but it is often unclear if such dynamic complexity is actually important for the network's regulatory functions [7, 8]. Here we found that the mitogen-activated protein kinase (MAPK) Fus3, a key regulator of the yeast mating pheromone response undergoes sustained oscillations in its phosphorylation/activation state during continuous pheromone exposure. These MAPK activity osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 27 publications
0
55
1
1
Order By: Relevance
“…Whether an artifactual augmentation of the oscillation propensity indeed takes place should be determined by independent control experiments not involving genetic or other perturbations of the cell. For instance, if the oscillatory responses are synchronized across the cell population, biochemical methods can and have been used to detect them, e.g., common Western blots [1013]. If, on the other hand, the oscillations are asynchronous, and thus would be masked in the average cell population response, one can resort to the analysis, such as flow cytometry or immunocytochemistry, that would allow taking snapshots of responses of single cells within a population at different times [14].…”
Section: The Howmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether an artifactual augmentation of the oscillation propensity indeed takes place should be determined by independent control experiments not involving genetic or other perturbations of the cell. For instance, if the oscillatory responses are synchronized across the cell population, biochemical methods can and have been used to detect them, e.g., common Western blots [1013]. If, on the other hand, the oscillations are asynchronous, and thus would be masked in the average cell population response, one can resort to the analysis, such as flow cytometry or immunocytochemistry, that would allow taking snapshots of responses of single cells within a population at different times [14].…”
Section: The Howmentioning
confidence: 99%
“…When unable to sense the gradient of the pheromone secreted by the cells of the opposite mating type, but sensing the presence of the pheromone in the immediate environment, yeast cells attempt to find the mating partner by trying to grow several projections sequentially in random directions. This periodic morphogenesis processes, that may ultimately leave a cell resembling a starfish, is controlled by a periodic activation and expression of a MAPK molecule regulating a multitude of the requisite genes [10]. The oscillation thus can control the duration of sequential phases of cell growth, with the MAPK activity localized to each new projection in preparation for a potential mating event.…”
Section: The Wherementioning
confidence: 99%
“…A majority of these rhythmic as well as arrhythmic stimuli lead to oscillations in second messengers (e.g. calcium, cAMP, PKA, MAPK) 1418 . Among these, the effect of frequency modulation of calcium oscillations on downstream transcription factor activation has been extensively studied using calcium-clamped cells 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of MAPK dynamics have predicted the existence of oscillatory kinase activation [99,100]. This hypothesis was proven by studies that focused on feedback regulation of MAPKs in mammalian and yeast cells [101][102][103][104][105]108]. Nakayama and colleagues investigated FGF-induced oscillatory Hes1 expression and ERK activation and found that a negative feedback phosphorylation of the guanine nucleotide exchange factor Sos (which activates Ras) by ERK [106] is required for this oscillation [101].…”
Section: Oscillatory Mapk Activationmentioning
confidence: 98%
“…Importantly, oscillatory MAPK dynamics have been difficult to address without single-cell measurement because averaging cell population responses will negate stochastic or asynchronous oscillation occurring in individual cells. Surprisingly, oscillatory activation of MAPK has also been found in the yeast Fus3 pathway [102], suggesting that some conserved regulatory mechanism may underlie the oscillatory dynamics of MAPK signaling.…”
Section: Oscillatory Mapk Activationmentioning
confidence: 98%